2004
DOI: 10.4049/jimmunol.173.3.1535
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of IFN Regulatory Factor-7 and IFN-α Production by Enveloped Virus and Lipopolysaccharide in Human Plasmacytoid Dendritic Cells

Abstract: Human plasmacytoid dendritic cells (PDC) are a major source of IFN-α upon exposure to enveloped viruses and TLR-7 and TLR-9 ligands. Although IFN regulatory factor-7 (IRF-7) is known to play an essential role in virus-activated transcription of IFN-α genes, the molecular mechanisms of IFN-α production in human PDC remain poorly understood. We and others have recently reported high constitutive levels of IRF-7 expression in PDC as compared with other PBMC. In this study, we demonstrate that both LPS and HSV up-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
120
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(132 citation statements)
references
References 71 publications
(97 reference statements)
10
120
1
1
Order By: Relevance
“…In PDC, IRF-7 is translocated to the nucleus within 2 h of stimulation with HSV, as shown by fluorescence microscopy (29). Preliminary experiments using this technique showed that cross-linking CD4 on PDC inhibited the nuclear translocation of IRF-7 in response to stimulation with HSV (data not shown).…”
Section: Cross-linking Bdca-2 Bdca-4 and Cd4 But Not Cd123 On Pdcmentioning
confidence: 89%
See 3 more Smart Citations
“…In PDC, IRF-7 is translocated to the nucleus within 2 h of stimulation with HSV, as shown by fluorescence microscopy (29). Preliminary experiments using this technique showed that cross-linking CD4 on PDC inhibited the nuclear translocation of IRF-7 in response to stimulation with HSV (data not shown).…”
Section: Cross-linking Bdca-2 Bdca-4 and Cd4 But Not Cd123 On Pdcmentioning
confidence: 89%
“…We postulate that these high levels of constitutive IRF-7 allow for the rapid expression of large quantities of IFN-␣ by PDC without the need for the aforementioned autocrine feedback loop. As in other cells, after viral stimulation, IRF-7 is phosphorylated, forms homodimers, and is translocated from the cytoplasm to the nucleus where it acts as a transcription factor for IFN-␣ genes (26,29,39). Because IRF-7 plays a large part in the production of IFN-␣, it may also play a pivotal role in the regulation of this cytokine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[64][65][66][67] Unlike other types of DCs, pDCs constitutively express high levels of IRF7. 68,69 Furthermore, treatment of pDCs with TLR9 ligands causes nuclear translocation of IRF7, and pDCs derived from IRF7-deficient mice are incapable of producing type I IFN in response to TLR7/8 and TLR9 ligands. 64,65 Thus, IRF7 is an essential transcription factor that regulates type I IFN induction in pDCs.…”
Section: Activation Of Irfs By Tlr7/8 and Tlr9mentioning
confidence: 99%